Supporting continuity of learning through assessment information sharing during transition : a comparison of early childhood and new entrant teachers beliefs, experiences and practices : a thesis in partial fulfilment of the requirements for the degree of Master of Education at Massey University, New Zealand - Fletcher, Melanie Irenee (Massey University, 2018)
Recent policy initiatives in New Zealand and internationally have focussed on the importance of continuity of learning for children transitioning to school. Effective transitions occur when continuity of learning is supported, with the sharing of assessment information seen as an important strategy to support continuity of learning for children transitioning to school. The perspectives of those directly involved in the sharing of assessment information between early childhood services and schools are underrepresented in the research literature. This study therefore aimed to compare the beliefs, experiences and practices of New Zealand early childhood and new entrant teachers regarding the sharing of assessment information to support children’s continuity of learning as they transition to school. Using self-administered online surveys, qualitative and quantitative data was gathered from early childhood and new entrant teachers in the Canterbury region. Analysis of the data identified several areas of similarity within and between the sectors including valuing continuity of learning whilst experiencing barriers to information sharing. A number of significant differences in perspectives emerged from the data, in particular regarding the utility of information shared, given the reported emphasis on the provision of strengths-based information. Findings suggest that inconsistent information sharing practices have led to new entrant teacher dissatisfaction with current processes, and a desire to see more formalised processes enacted. The study identifies several recommendations, including that there is a need for greater collaboration and communication between the two education sectors to ensure assessment information is shared effectively. The provision of guidelines and the development of a template would improve the utility of the information supplied and ensure a more consistent approach to information sharing. The sharing of assessment information should be made compulsory, thus removing the inconsistencies in information sharing practices that are currently occurring.
Keywords: Readiness for school; New Zealand; Educational planning; Early childhood education; Evaluation; Early childhood teachers; Primary school teachers; Attitudes